Earthquake geo facts - Amson-Bradshaw, Georgia (Geofacts (Crabtree Publishing Company), 2018)
Examines the geographical science behind earthquakes, highlighting several major quakes that occurred over the years and the aftermath that followed them. Includes a glossary, text-related questions with an answer key, resources for further information, diagrams, maps, and color photographs.